Cracking behavior of asphalt pavement with a graded gravel layer based on computational granular mechanics. (22nd August 2022) - Shan, Jingsong; Zhang, Yuan; Wu, Shuyin; Wu, Qiulin; Jiao, Yuying; Du, Yang
Highlights: Reflective cracking behavior of asphalt pavement was studied. Anti-cracking mechanism of graded gravel was analyzed. Discrete element method is used to establish the numerical model. The development of cracks was monitored and tracked. Abstract: The reflective cracking is still a critical issue to be solved in the semi-rigid base asphalt pavements. In this study, the discrete element method (DEM) is used to study the reflection cracks of semi-rigid base asphalt pavement with a graded gravel interlayer at the meso level. The generation and development of internal meso cracks in asphalt pavements under vehicle loads were simulated and analyzed. The simulation results show that in the semi-rigid base asphalt pavement, the preset cracks extend from the tip to the surface layer and form reflective cracks in the direction of the oblique loading plate. With the increase in surface thickness, the development trend of the cracks slows down, and the total amount of meso cracks in the pavement decreases. The reflective cracking is reduced in the asphalt pavement with a graded crushed stone base, and the distribution position is relatively discrete. Under the same surface thickness, the number of meso cracks decreases with the thickness of the graded crushed stone base. It indicates that the graded gravel can effectively prevent the development of reflective cracking in asphalt pavements.